Differential Immune Gene Expression Profiles in Susceptible and Resistant Full-Sibling Families of Atlantic Salmon (Salmo Salar) Challenged with Infectious Pancreatic Necrosis Virus (Ipnv) - Sandino-Garcia, A; Imarai-Bahamonde, C; Romeo-Nunez, J; Reyes-Cerpa, S; Vallejos-Vidal, E (Elsevier Ltd, 2015)
This study aims to identify at the expression level the immune-related genes associated with IPN-susceptible and resistant phenotypes in Atlantic salmon full-sibling families. We have analyzed thirty full-sibling families infected by immersion with IPNV and then classified as resistant or susceptible using a multivariate survival analysis based on a gamma-Cox frailty model and the Kaplan-Meier mortality curves. In four families within each group head kidneys were pooled for real-time PCR and one-color salmon-specific oligonucleotide microarray (21K) analysis at day 1 and 5 post-infection. Transcripts involved in innate response (IL-6, IFN-α), antigen presentation (HSP-70, HSP-90, MHC-I), TH1 response (IL-12, IFN-γ, CRFB6), immunosuppression (IL-10, TGF-β1) and leukocyte activation and migration (CCL-19, CD18) showed a differential expression pattern between both phenotypes, except in IL-6. In susceptible families, except for IFN-γ, the expressions dropped to basal values at day 5 post-infection. In resistant families, unlike susceptible families, levels remained high or increased (except for IL-6) at day 5. Transcriptomic analysis showed that both families have a clear differential expression pattern, resulting in a marked down-regulation in immune related genes involved in innate response, complement system, antigen recognition and activation of immune response in IPN-resistant. Down-regulation of genes, mainly related to tissue differentiation and protein degradation metabolism, was also observed in resistant families. We have identified an immune-related gene patterns associated with susceptibility and resistance to IPNV infection of Atlantic salmon. This suggests that a limited immune response is associated with resistant fish phenotype to IPNV challenge while a highly inflammatory but short response is associated with susceptibility. © 2015 Elsevier Ltd.